O brincar dançante: a criança e sua inerente necessidade de brincar e se-movimentar pela dança - Silva, Taise Motta Rensch da (2018)
This study aimed essentially to know children better, to understand the world of life and the world of movement, their play and move-yourself in times of technology and lack of time to be a child. Some issues were taken into consideration: does the child still have time to play and move-yourself freely? What are your possibilities for jokes? And your involvement with the new technologies? Therefore, it is necessary to place the child in the various historical processes, bringing a little about the history of the child, the emergence of day care centers and physical education in Early Childhood Education. Thus, the objective of the research is: to investigate in literature the daily oppression of children to become productive adults, and the possibility of gradual loss of one of their vital needs, which is to play and move-yourself freely and fully, and if a "dancing play" can rescue and reintroduce the child in this world of play and move-yourself. This research was done through a theoretical research, in order to dialogue about authors and new knowledge. The work presents fundamentals with some critics about play of the child who does not have time to play and move-yourself in the present day, and is being inserted early in childhood education institutions, speeding its development to the adult world. The intention is not to solve this problem, but make an alert for adults, teachers and children's institutions, and to take more into account the Child Being in its essence, valuing its potentialities and possibilities, through play and move-yourself that can be introduced or reintroduced through a "dancing play".